Prebiotics and Probiotics Potential Benefits in Nutrition and Health - Franco-Robles, Elena; Ramírez-Emiliano, Joel (Biochemistry, 2020)
Probiotic bacteria are found in the intestinal microbiota of the host and favor multiple metabolic reactions. Prebiotics provide food for probiotic bacteria and have an effect on their own performance in favor of host health. Numerous metabolic and immunological mechanisms are involved in its effects. Probiotics have been studied for several decades and their use for human consumption is still unclear. However, new types of molecules with prebiotic functions and components of probiotic bacteria with therapeutic potential are still being studied. The versatility of these molecules makes their incorporation into human food and animal diets feasible. This book is a compendium of recent scientific information on the use of probiotics and prebiotics for the benefit of human and animal health.